2021
DOI: 10.1210/clinem/dgab433
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Adiposity Associated With Expanded Effector Memory CD8+ and Vδ2+Vγ9+ T Cells

Abstract: Context Adult obesity is associated with chronic low-grade inflammation and may give rise to future chronic disease. However, it is unclear whether adiposity-related inflammation is already apparent at young age. Objective To study associations between child’s adiposity measures with circulating monocytes and naive and memory subsets in CD4, CD8, and γδ T-cell lineages. Design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 64 publications
0
2
0
2
Order By: Relevance
“…However, a study of 18 women with morbid obesity, revealed that only IFNγ producing NK cells but not γδ (or CD4 or CD8) T cells were positively associated with obesity, IR and hemoglobin A1C (HBA1C) levels [63]. The effect of obesity resulting in the reduction of γδ T cells in the PB may moreover, be age-dependent, since an analysis of PB of 890 children using magnetic resonance imaging (MRI) and dual-energy X-Ray absorptiometry, revealed that higher Vγ9δ2 cells were found in patients with higher fat mass index, visceral fat index, and android to gynoid ratio [64].…”
Section: γδ T Cells In Human Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, a study of 18 women with morbid obesity, revealed that only IFNγ producing NK cells but not γδ (or CD4 or CD8) T cells were positively associated with obesity, IR and hemoglobin A1C (HBA1C) levels [63]. The effect of obesity resulting in the reduction of γδ T cells in the PB may moreover, be age-dependent, since an analysis of PB of 890 children using magnetic resonance imaging (MRI) and dual-energy X-Ray absorptiometry, revealed that higher Vγ9δ2 cells were found in patients with higher fat mass index, visceral fat index, and android to gynoid ratio [64].…”
Section: γδ T Cells In Human Obesitymentioning
confidence: 99%
“…Obese adults PB decrease Decrease of γδ cells in the PB, which are less capable of IFNγ production and express less of IL-2R and IL-7R [58] Obese women PB decrease Decrease, less IL-2 and IFNγ production [59] Obese adults Decrease Vγ9δ2/γδ ratio in PB [61] Morbid Obesity adults PB IFNγ + γδ T cells are not correlated with obesity [63] Obese children Increase of Vγ9δ2 cells in PB [64] Obese adults with OSA…”
Section: Number and Function Of γδ T Cells Referencementioning
confidence: 99%
“…Так, бесспорными являются общесистемные изменения иммунной функции при ожирении, описанные для реакций на инфекцию (в том числе определяющее более тяжелое течение COVID-19), вакцинацию и злокачественные новообразования [22]. Новейшие исследования в Нидерландах продемонстрировали избыточное количество некоторых субпопуляций лимфоцитов (Vδ2 +Vγ9 + иCD8 +TEMRO) у детей с более высоким индексом висцерального жира, что может свидетельствовать о наличии у них хронического воспаления, так же как и у взрослых пациентов с ожирением [23]. Более того, систематический анализ 26 обзоров, посвященных изучению взаимосвязи между ожирением у детей (или их матерей во время беременности) и работой иммунной системы ребенка подтвердил наличие ассоциации между детским ожирением и значительными сдвигами в сывороточных уровнях про-и противовоспалительных цитокинов и протеинов, а также количеством и активностью иммунокомпетентных клеток [24].…”
Section: общность патогенетическихunclassified
“…Иммунный характер ассоциации между ожирением и аллергией подтверждают последние исследования в Голландии, которые продемонстрировали избыточное количество некоторых субпопуляций лимфоцитов (Vδ2 + Vγ9 + и CD8 + TEMRO) у детей с более высоким индексом висцерального жира, что может свидетельствовать о наличии у них хронического воспаления [12]. Несбалансированное питание, приводящее к снижению важных нутриентов (про-и пребиотиков, омега-3-полиненасыщенных жирных кислот, фолатов), нарушению кишечного микробиома, отвечающих за иммунную регуляцию, дефицит витамина D, ассоциированного с ожирением, а также с повышенным уровнем циркулирующих медиаторов воспаления, определяют риск развития аллергических заболеваний [13][14][15][16][17].…”
unclassified